Análise estrutural de reservatórios cilíndricos em concreto armado: estudo comparativo através de um projeto modelo - Oliveira, José Lucas Pessoa de (Universidade Federal Rural do Semi-Árido, 2017)
A study on cylindrical reservoirs in reinforced concrete is carried out in this work. We present the theoretical conceptualization available in the literature for the design of these structures, with a chapter dedicated to methodologies of structural analysis, in addition, some details of design and execution are presented. In order to compare the results of these methodologies, the study of a cylindrical reservoir of reinforced concrete for the storage of 1500 m3 of drinking water is done. This model, previously conceived, is analyzed by four methods: Classic Theory, Finite Element Method (MEF), Hangan-Soare Abacus and Flat Portico analogy. These four methods of analysis will be used for three reservoir models, which evaluate the bonding conditions between the wall and the bottom slab, considering a rigid or elastic joint. In the sizing step, a maximum aperture of the cracks is limited, and the working tension in the steel is calculated, using the maximum efforts found between the methods. It was observed that there was good convergence in the results for the different models evaluated, with greater discrepancies for the results obtained through the FEM, due to several factors that can occur in the modeling performed in finite element software. All other methods presented satisfactory results for design purposes. It is concluded that special attention should be given to modeling structures in finite element software, since these are very sensitive to the parameters used, and in order to corroborate the results, it is quite valid to apply the practical methods.
Keywords: Reservatório cilîndrico; concreto armado; MEF; cascas; membranas; cylindrical reservoir; armed concrete; shells; membranes; ENGENHARIAS::ENGENHARIA CIVIL